Big data analytics for entrepreneurial orientation: Concepts, challenges and applications - Bekkouche, Latifa (University of Eloued جامعة الوادي, 2022)
The purpose of this study was to explore the processes leading to achieving entrepreneurial orientation through big data analytics. In doing so, we used the narrative approach to analyse thematically the key elements of the events, and because we found it useful in gathering, summarising, and synthesising several numbers of literature on these concepts and their practice. Therefore, we tried to provide readers with a comprehensive background for understanding current knowledge and highlighting the significance of research in understanding these cognate areas. As the results of the study, this review identified the knowledges on what is available on entrepreneurial orientation and big data analytics, thus helping to inform future research in this area, particularly important questions needed to be resolved to make this research area attractive.
مداخلة. الملتقى الدولي الافتراضي: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية: الفرص، التحديات والافاق". 18 جوان 2022. كلية العلوم الاقتصادية والتجارية وعلوم التسيير. جامعة الوادي.
Keywords: Big Data Analytics; Entrepreneurial Orientation; Big Data; entrepreneurship; entrepreneur.; تحليلات البيانات الضخمة، التوجه الريادي، البيانات الضخمة، ريادة الأعمال، المقاول